From stress fiber to focal adhesion: a role of actin crosslinkers in force transmission - Katsuta, Hiroki; Sokabe, Masahiro; Hirata, Hiroaki (Frontiers in Cell and Developmental Biology, 2024)
The contractile apparatus, stress fiber (SF), is connected to the cell adhesion machinery, focal adhesion (FA), at the termini of SF. The SF-FA complex is essential for various mechanical activities of cells, including cell adhesion to the extracellular matrix (ECM), ECM rigidity sensing, and cell migration. This mini-review highlights the importance of SF mechanics in these cellular activities. Actin-crosslinking proteins solidify SFs by attenuating myosin-driven flows of actin and myosin filaments within the SF. In the solidified SFs, viscous slippage between actin filaments in SFs and between the filaments and the surrounding cytosol is reduced, leading to efficient transmission of myosin-generated contractile force along the SFs. Hence, SF solidification via actin crosslinking ensures exertion of a large force to FAs, enabling FA maturation, ECM rigidity sensing and cell migration. We further discuss intracellular mechanisms for tuning crosslinker-modulated SF mechanics and the potential relationship between the aberrance of SF mechanics and pathology including cancer.